Method for preparing Prussian blue compound through lateral growth mechanism

Through lateral growth mechanism and ultrasonic treatment, low-deficiency Prussian blue compounds were prepared, which solved the problem of difficult preparation of Prussian blue compounds in the prior art and many defects, and improved the electrochemical performance of sodium ion batteries.

CN119612551APending Publication Date: 2025-03-14SICHUAN UNIVERSITY OF SCIENCE AND ENGINEERING
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411871891.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

It is difficult to prepare low-defect Prussian blue compounds in the prior art, resulting in a decrease in the number of sodium ions deintercalation during charging and discharging of sodium ion batteries, affecting battery performance.

Method used

Through the lateral growth mechanism, the mixed solution was gradually added dropwise and heated under an inert atmosphere and ultrasonic treatment to prepare a cubic phase Prussian blue compound with a transition metal gradient substituted by transition metal.

Benefits of technology

The preparation of low-defect, sodium-rich Prussian blue compounds was achieved, and the integrity of the crystal structure and the electrochemical performance of sodium ion batteries were improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612551A_ABST
    Figure CN119612551A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a Prussian blue compound through a lateral growth mechanism, and belongs to the technical field of material preparation. On the premise of not changing the overall frame structure of the existing Prussian blue, the low-potential Prussian blue compound FeR [Fe (CN) 6] with different nickel substitution amounts is obtained by adjusting the types and contents of transition metal elements and substituting atoms bridged with cyanide ions. According to the present invention, by using the anisotropy of the compound, the formation of the cubic phase crystal structure through the lateral growth mechanism is clarified from the atomic level, the preparation of the Prussian blue compound can be completed within a short time through the thermodynamic and dynamic condition setting, and the method has characteristics of no toxicity, no harm, no excess impurity generation, and increase of the synthesis yield;
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material preparation, and more specifically relates to a method for preparing Prussian blue compounds through a lateral growth mechanism. Background Art

[0002] Sodium-ion batteries are the most representative and promising non-lithium secondary batteries. Although sodium-ion batteries have a low specific charge, their low price and abundant resources give them great advantages in large-scale energy storage systems. The selection of positive electrode materials for sodium-ion batteries has a significant impact on their performance. With the development of sodium-ion batteries, Prussian blue compounds with mild synthesis process, stable open frame structure and weak interaction with interstitial ions have become common positive electrode materials for sodium-ion batteries.

[0003] The molecular formula of Prussian blue compounds is A x M a [M b (CN)6] y nH2O, where A is an alkali metal, M a and M b They are high-spin and low-spin transition metals, respectively. They are bridged with cyanide ions to form alternating weakly coordinated octahedra (M a N6) and strongly coordinated octahedron (M b C6), the two types of octahedrons are combined to obtain an open and stable cubic structure. At the same time, due to different preparation conditions, M a and M b It presents a combination of multiple valence states, so that during the charging and discharging process of the sodium ion battery, (like Figure 1 a), although all three structures provide spacious ion channels for sodium ion diffusion, the randomly appearing M b (CN)6 vacancies increase the amount of bound water, which reduces the number of octahedral gaps, thereby reducing the number of sodium ions that can be deintercalated. Therefore, the number of vacancies is related to the transition metal M a and M b If we can continue to construct Prussian blue compounds with low vacancy content and rich sodium ions in the gaps on this basis, it will be of great benefit to the development of sodium ion batteries. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing Prussian blue compounds through a lateral growth mechanism, so as to solve the problems existing in the above-mentioned prior art and realize the preparation of low-defect Prussian blue compounds.

[0005] To achieve the above object, the present invention provides the following solutions:

[0006] One of the technical solutions of the present invention is to provide a Prussian blue compound, wherein the chemical formula of the Prussian blue compound is FeR[Fe(CN)6], and the Prussian blue compound includes two weakly coordinated octahedrons FeN6 and RN6, and one strongly coordinated octahedron FeC6, wherein R represents a transition metal, and the transition metal includes nickel, manganese or cobalt;

[0007] In the weakly coordinated octahedron, Fe and R are in a high spin state;

[0008] The Fe in the strongly coordinated octahedron is in a low spin state;

[0009] The Prussian blue compound also includes alkali metal ions, and the alkali metal ions are located in the interstitial positions of the octahedron.

[0010] Preferably, the alkali metal ions include sodium ions.

[0011] Under the premise of not changing the overall framework structure of the existing Prussian blue, the invention modifies the existing Prussian blue by adjusting the type and content of the transition metal element therein, thereby obtaining low-vacancy Prussian blue compounds (FeR[Fe(CN)6]) with different transition metal substitution amounts.

[0012] The second technical solution of the present invention is to provide a method for preparing the Prussian blue compound, comprising the following steps:

[0013] Mixing a transition metal salt, ferrous chloride and an anhydrous organic solvent to obtain a first mixed solution; mixing sodium ferrocyanide, a reducing agent and an anhydrous organic solvent to obtain a second mixed solution;

[0014] Under an inert atmosphere, dropwise adding the first mixed solution into the second mixed solution and heating for reaction to obtain the Prussian blue compound;

[0015] The transition metal salt includes nickel chloride, manganese chloride or cobalt chloride.

[0016] The Gibbs free energy G=H-TS<0 in the preparation process indicates that as the temperature increases, entropy plays an increasingly important role in the entire reaction system. Therefore, in the process of gradually adding the second mixed solution to the first mixed solution, the precipitation rate of the blue precipitate (Prussian blue compound) increases continuously.

[0017] The lateral growth mechanism of the Prussian blue compound is described by the obvious anisotropic characteristics of the compound, and the preparation of Prussian blue compound crystals with a regular hexahedral structure is achieved; by controlling the amount of the first mixed solution added to control and reduce the number of vacancies in the crystal structure, the integrity of the crystal structure is significantly improved, and a sodium-rich Prussian blue compound is prepared.

[0018] Preferably, the total concentration of transition metal salt and ferrous chloride in the first mixed solution is 10mM, wherein the concentration of ferrous chloride is 8-10mM, the concentration of transition metal salt is 0-2mM, and the concentration of transition metal salt is not 0; the concentration of sodium ferrocyanate in the second mixed solution is 10mM; wherein the transition metal will gradually replace iron to form two weakly coordinated octahedra FeN6 and RN6 (wherein R represents a transition metal, and the transition metal includes nickel, manganese or cobalt).

[0019] Optionally, the ferrous chloride, nickel chloride and sodium ferrocyanide are anhydrous ferrous chloride, anhydrous nickel chloride and anhydrous sodium ferrocyanate, respectively.

[0020] Optionally, the anhydrous organic solvent is anhydrous ethanol; and the reducing agent includes one or more of vitamin A, vitamin C, vitamin E and β-carotene.

[0021] Preferably, the amount of the reducing agent used is 0.1 to 1 times the molar equivalent of ferrous chloride.

[0022] Preferably, the step of adding the first mixed liquid to the second mixed liquid and heating the liquid comprises: under an inert atmosphere, gradually adding the first mixed liquid to the second mixed liquid subjected to ultrasonic treatment, heating the liquid while adding the first mixed liquid, ensuring that the temperature is raised to the heating reaction temperature while the adding is completed, and then keeping the temperature.

[0023] The reaction mechanism of the present invention is as follows: firstly, a neutral anhydrous solvent system is used, and sodium ferrocyanide is prepared into a suspension slightly soluble in an anhydrous organic solvent under the protection of an inert atmosphere, so as to avoid the presence of toxic cyanide ions in the solution due to the dissociation of some ferrocyanide ions, thereby reducing the product yield; secondly, ferrous chloride and a transition metal salt are gradually added dropwise under the premise of maintaining an excess of sodium ferrocyanide, so as to form a thermodynamic condition G=H-TS<0 that is extremely favorable for the generation of a Prussian blue compound, and at the same time, the presence of a reducing agent makes Fe in the solution 2+ Not oxidized to Fe 3+ The possibility of increasing the temperature while gradually adding the first mixed solution with the assistance of ultrasound, Fe 2+ and transition metal ions with less content will simultaneously react with [Fe(CN)6] 4- The new bridges are formed, which is beneficial to reduce the probability of crystal vacancies. Finally, the prepared Prussian blue compounds include two weakly coordinated octahedrons FeN6 and RN6 and one strongly coordinated octahedron FeC6, where R represents a transition metal and Fe bonded to nitrogen atoms. 2+ and transition metal ions are located in weakly coordinated octahedrons, but both (Fe 2+The difference in radius of the two octahedra (and transition metal ions) makes the anisotropy of Prussian blue compounds more obvious. The bridging of the two octahedra shows selectivity when the temperature continues to rise. Through the lateral growth of the crystal, the vacancies occupied by free water are squeezed out as much as possible, thereby improving the crystal integrity of Prussian blue compounds.

[0024] The invention adopts a strategy of dripping a first mixed solution of nickel chloride and ferrous chloride into a second mixed solution of excess sodium ferrocyanide in small amounts for multiple times and gradually raising the temperature, thereby changing the thermodynamic conditions of the reaction system, making full use of the characteristic of extremely low free energy barrier required for the generation of Prussian blue compounds to prepare cubic phase Prussian blue compounds with gradient substitution of transition metals; utilizing the concentration of ultrasonic energy, the kinetic reaction rate of the reaction system is increased, ensuring that the reaction system consumes less time, and saving energy consumption.

[0025] Preferably, the inert gas in the inert atmosphere includes nitrogen or argon, and the flow rate of the inert gas is 0.05-0.1 m 3 / h; the ultrasonic power of the ultrasonic treatment is 100-200W; the dropping acceleration is 24-36s / mL; the heating rate is 1-2°C / min; the temperature of the heating reaction is 60-80°C, and the insulation time of the heating reaction is 0.5-1.5h.

[0026] Preferably, after the reaction is completed, the process further comprises the steps of sedimentation and drying.

[0027] Furthermore, the sedimentation includes centrifugal sedimentation, and the number of sedimentation is 3 to 4 times; the drying temperature is 120° C., the drying vacuum degree is 0.005 to 0.01 MPa, and the drying time is 24 hours.

[0028] The third technical solution of the present invention is to provide the application of the Prussian blue compound in the preparation of sodium ion full battery.

[0029] The fourth technical solution of the present invention is to provide a sodium ion full battery, wherein the positive electrode material of the sodium ion battery is the Prussian blue compound.

[0030] The present invention discloses the following technical effects:

[0031] 1. The present invention selects environmentally friendly raw materials such as ferrous chloride, nickel chloride and sodium ferrocyanide, which plays a certain role in protecting the ecological environment, realizes the rational use of natural resources, and maintains the resource economic value system.

[0032] 2. The preparation method of the present invention is simple and efficient, and has excellent thermodynamic conditions. The reaction avoids the high demand for complexing agents, and Prussian blue compounds with excellent performance can be prepared without using complexing agents.

[0033] 3. The present invention utilizes the protection of inert atmosphere, the antioxidant property of reducing agent and the characteristics of anhydrous ethanol as neutral reagent to eliminate Fe 2+ It may be oxidized, and finally a dark blue precipitate is obtained, namely, a Prussian blue compound;

[0034] 4. The present invention utilizes the characteristics of good directionality, strong penetration and concentrated energy of ultrasonic treatment to make Ni 2+ , Fe 2+ Complete bridging reduces the number of vacancies and reduces the loss of raw materials.

[0035] 5. The present invention adopts the strategy of adding a small amount of ferrous chloride and nickel chloride mixed solution repeatedly and heating the mixture to optimize the thermodynamic and kinetic conditions of the reaction so that the transition metal ions react with Fe 2+ Gradient replacement becomes possible.

[0036] 6. The present invention is based on a coprecipitation method, and the product preparation can be completed in a short time. The preparation method is non-toxic and harmless, and the yield of Prussian blue compounds is improved.

[0037] 7. The present invention proposes a preparation method of a Prussian blue compound based on the lateral growth principle, which explains the formation of a cubic phase crystal structure at the atomic level without the appearance of excess impurities. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 The structure of the Prussian blue compound and the nickel substitution of the high spin position Fe in the embodiment of the present invention are shown in FIG. 2+ Schematic diagram of the present invention, where a is the three crystal forms and the corresponding two types of octahedrons, b is the standard structure of Prussian blue crystal, c is the Prussian blue crystal structure containing free water (vacancy), and d is the nickel substitution of Fe at the high spin position. 2+ Schematic diagram of Figure 1 In a, the octahedra of different colors represent weakly coordinated octahedra (M a N6) and strongly coordinated octahedron (M b C6), M a and M b They are high-spin and low-spin transition metals, respectively. The red ball represents sodium. Figure 1 b and Figure 1 In c, M is a transition metal;

[0039] Figure 2 Figure 1 is a diagram of the lateral growth principle of Prussian blue compounds, where a is a diagram of the discontinuous lateral growth mechanism and b is a diagram of the continuous lateral growth mechanism;

[0040] Figure 3The XRD patterns of the Prussian blue compounds obtained in Examples 1, 2 and 3, wherein PB indicates that the first mixed solution is a 10 mM pure ferrous chloride solution, LNGPB indicates that the first mixed solution contains 0.9 mmol ferrous chloride and 0.1 mmol nickel chloride, and HNGPB indicates that the first mixed solution contains 0.8 mmol ferrous chloride and 2 mmol nickel chloride;

[0041] Figure 4 This is a SEM image of the Prussian blue compound obtained in Example 1;

[0042] Figure 5 This is a SEM image of the Prussian blue compound obtained in Example 2;

[0043] Figure 6 This is a SEM image of the Prussian blue compound obtained in Example 3;

[0044] Figure 7 The figure is a rate cycle curve diagram after the Prussian blue compounds obtained in Example 1, Example 2, and Example 3 are assembled into a sodium ion full battery as the positive electrode, wherein PB means that the first mixed solution is a 10mM ferrous chloride solution; LNGPB means that there are 0.9mmol ferrous chloride and 0.1mmol nickel chloride in the first mixed solution; HNGPB means that there are 0.8mmol ferrous chloride and 0.2mmol nickel chloride in the first mixed solution;

[0045] Figure 8 This is a rate cycle curve diagram of a sodium ion full battery assembled with the Prussian blue compound obtained in Comparative Example 1 as a positive electrode;

[0046] Fig. 9 This is a rate cycle curve diagram of a sodium ion full battery assembled with the Prussian blue compound obtained in Comparative Example 2 as the positive electrode;

[0047] Fig.10 This is a rate cycle curve diagram of a sodium ion full battery assembled with the Prussian blue compound obtained in Comparative Example 3 as the positive electrode. DETAILED DESCRIPTION

[0048] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0049] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0050] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0051] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present invention description and examples are exemplary only.

[0052] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0053] The lateral growth mechanism described in the present invention (such as Figure 2 The details are as follows:

[0054] 1. Intermittent lateral growth mechanism: Compared with the continuous growth mechanism of metals and alloys, Prussian blue compounds show more anisotropy. During the grain growth process, the free energy of some crystal faces is extremely low, showing a plane or even a concave surface. In the subsequent precipitation process, it tends to grow laterally along the plane. When it touches the edge of the nucleation substrate, the lateral growth stops;

[0055] 2. Continuous lateral growth mechanism: Due to the anisotropy of Prussian blue compounds, the free energy of some crystal planes is very low. In the process of non-uniform nucleation, they face defects caused by impurity atoms, such as screw dislocations or twin boundaries, both of which provide steps for lateral growth. At this time, the thermal enthalpy change caused by the number of broken bonds between adjacent grains is much lower than the entropy change caused by temperature, so that the lateral growth does not stop in an ideal environment.

[0056] Prussian blue compounds are affected by impurity nucleation bases, resulting in an incomplete lateral growth process, a high probability of crystal defects, and an unclear cubic phase structure. The present invention reduces the possibility of crystal water occupying vacancies by regulating thermodynamic conditions (gradient heating) and kinetic conditions (excess second mixed solution and a small amount of first mixed solution), thereby obtaining Prussian blue compounds with interstitial sodium ions.

[0057] The following examples include both a discontinuous lateral growth mechanism and a continuous lateral growth mechanism in the preparation of Prussian blue compounds.

[0058] The scanning electron microscope used to obtain the SEM images of Prussian blue compounds is Sigma300 (made in: CarlZeiss Microscopy Limited); the integrated constant temperature battery test box used to test the electrochemical performance of the sodium ion full battery is MIHW-200-160CH (made in: Shenzhen Xinwell Electronics Co., Ltd.); the ultrasonic crusher is ZOLLO-650Y (Shanghai Zuole Instrument Co., Ltd.); the anhydrous ethanol used is AR grade anhydrous ethanol.

[0059] Example 1

[0060] This embodiment provides a method for preparing a Prussian blue compound by a lateral growth mechanism, and the specific steps are as follows:

[0061] (1) Weigh 0.8 mmol of ferrous chloride (FeCl2) and 0.2 mmol of nickel chloride (NiCl2) and dissolve them in 100 mL of anhydrous ethanol to form a mixed solution with a total concentration of 10 mM;

[0062] (2) Weigh 1 mmol of sodium ferrocyanide (Na4[Fe(CN)6]) and dissolve it in 100 mL of anhydrous ethanol to form a light yellow sodium ferrocyanide suspension solution with a concentration of 10 mM, and add vitamin E thereto to ensure that vitamin E is the only source of reducing agent. The amount of vitamin E used is 1 times the molar equivalent of ferrous chloride;

[0063] (3) In nitrogen atmosphere (0.05m 3 / h) protection, subjecting the sodium ferrocyanide solution to ultrasonic treatment (ultrasonic power of 150W), and heating it to 70°C at a heating rate of 1°C / min, while intermittently adding the mixed solution obtained in step (1) thereto, ensuring that the mixed solution is just added when the temperature reaches 70°C, the mixed solution addition speed is 30s / mL, and the sodium ferrocyanide solution gradually changes from light yellow to dark blue during the addition process;

[0064] (4) After the addition was completed, the mixture was kept warm for 1 h, and the suspension was centrifuged (3 times). The precipitate was retained and dried at 120° C. in vacuum (vacuum degree: 0.01 MPa) for 24 h to obtain a Prussian blue compound (denoted as HNGPB) with a yield of 92.70%.

[0065] The XRD and SEM images of the Prussian blue compounds obtained in this example are as follows: Figure 3 and Figure 4 As shown, analysis shows that the Prussian blue compound prepared in this example has a cubic phase structure.

[0066] The electrochemical performance of a sodium ion full battery was tested by assembling the Prussian blue compound obtained in this example as the positive electrode, the polyanion compound as the negative electrode, and sodium hexafluorophosphate as the electrolyte. The test temperature was 25° C. and the test voltage range was 1.5 to 4.5 V.

[0067] It was determined that at 0.1C, the initial specific capacity was 99.7 mAh / g ( Figure 7 The capacity retention rate is 88%.

[0068] Example 2

[0069] This embodiment provides a method for preparing a Prussian blue compound by a lateral growth mechanism, and the specific steps are as follows:

[0070] (1) Weigh 0.9 mmol of ferrous chloride (FeCl2) and 0.1 mmol of nickel chloride (NiCl2) and dissolve them in 100 mL of anhydrous ethanol to form a mixed solution with a total concentration of 10 mM;

[0071] (2) Weigh 1 mmol of sodium ferrocyanide (Na4[Fe(CN)6]) and dissolve it in 100 mL of anhydrous ethanol to form a light yellow turbid sodium ferrocyanide solution with a concentration of 10 mM, and add vitamin E thereto to ensure that vitamin E is the only source of reducing agent. The amount of vitamin E used is 1 times the molar equivalent of ferrous chloride;

[0072] (3) In nitrogen atmosphere (0.05m 3 / h) protection, subjecting the sodium ferrocyanide solution to ultrasonic treatment (ultrasonic power of 150W), and heating it to 70°C at a heating rate of 1°C / min, while intermittently adding the mixed solution obtained in step (1) thereto, ensuring that the mixed solution is just added when the temperature reaches 70°C, the mixed solution addition speed is 30s / mL, and the sodium ferrocyanide solution gradually changes from light yellow to dark blue during the addition process;

[0073] (4) After the addition was completed, the mixture was kept warm for 1 h, and the suspension was centrifuged (3 times). The precipitate was retained and dried at 120° C. in vacuum (vacuum degree: 0.01 MPa) for 24 h to obtain a Prussian blue compound (denoted as LNGPB) with a yield of 91.30%.

[0074] The XRD and SEM images of the Prussian blue compounds obtained in this example are as follows: Figure 3 and Figure 5 As shown, analysis shows that the Prussian blue compound prepared in this example has a cubic phase structure.

[0075] The electrochemical performance of a sodium ion full battery was tested by assembling the Prussian blue compound obtained in this example as the positive electrode, the polyanion compound as the negative electrode, and sodium hexafluorophosphate as the electrolyte. The test temperature was 25° C. and the test voltage range was 1.5 to 4.5 V.

[0076] It was determined that at 0.1C, the initial specific capacity was 79.7 mAh / g (e.g. Figure 7 The capacity retention rate is 87%.

[0077] Example 3

[0078] This embodiment provides a method for preparing a Prussian blue compound by a lateral growth mechanism, and the specific steps are as follows:

[0079] (1) Weigh 1 mmol of ferrous chloride (FeCl2) and dissolve it in 100 mL of anhydrous ethanol to form a solution with a concentration of 10 mM;

[0080] (2) Weigh 1 mmol of sodium ferrocyanide (Na4[Fe(CN)6]) and dissolve it in 100 mL of anhydrous ethanol to form a light yellow turbid sodium ferrocyanide solution with a concentration of 10 mM, and add vitamin E thereto to ensure that vitamin E is the only source of reducing agent. The amount of vitamin E used is 1 times the molar equivalent of ferrous chloride;

[0081] (3) In nitrogen atmosphere (0.05m 3 / h) protection, subjecting the sodium ferrocyanide solution to ultrasonic treatment (ultrasonic power of 150W), and heating it to 70°C at a heating rate of 1°C / min, while intermittently adding the mixed solution obtained in step (1) thereto, ensuring that the mixed solution is just added when the temperature reaches 70°C, the mixed solution addition speed is 30s / mL, and the sodium ferrocyanide solution gradually changes from light yellow to dark blue during the addition process;

[0082] (4) After the addition was completed, the mixture was kept warm for 1 h, and the suspension was centrifuged (3 times). The precipitate was retained and dried at 120° C. in vacuum (vacuum degree: 0.01 MPa) for 24 h to obtain a Prussian blue compound (referred to as pure PB) with a yield of 90.20%.

[0083] The XRD and SEM images of the Prussian blue compounds obtained in this example are as follows: Figure 3 and Figure 6 As shown, analysis shows that the Prussian blue compound prepared in this example has a cubic phase structure.

[0084] The electrochemical performance of a sodium ion full battery was tested by assembling the Prussian blue compound obtained in this example as the positive electrode, the polyanion compound as the negative electrode, and sodium hexafluorophosphate as the electrolyte. The test temperature was 25° C. and the test voltage range was 1.5 to 4.5 V.

[0085] It was determined that at 0.1C, the initial specific capacity was 79.9 mAh / g ( Figure 7 The capacity retention rate is 87%.

[0086] Comparative Example 1

[0087] This comparative example provides a method for preparing a cobalt-substituted Prussian blue compound, and the specific steps are as follows:

[0088] (1) Weigh 0.8 mmol of ferrous chloride (FeCl2) and 0.2 mmol of cobalt chloride (CoCl2) respectively and dissolve them in 100 mL of anhydrous ethanol to form a mixed solution with a total concentration of 10 mM;

[0089] (2) Weigh 1 mmol of sodium ferrocyanide (Na4[Fe(CN)6]) and dissolve it in 100 mL of anhydrous ethanol to form a light yellow sodium ferrocyanide suspension solution with a concentration of 10 mM, and add vitamin E thereto to ensure that vitamin E is the only source of reducing agent. The amount of vitamin E used is 1 times the molar equivalent of ferrous chloride;

[0090] (3) In nitrogen atmosphere (0.05m 3 / h) protection, subjecting the sodium ferrocyanide solution to ultrasonic treatment (ultrasonic power of 150W), and heating it to 70°C at a heating rate of 1°C / min, while intermittently adding the mixed solution obtained in step (1) thereto, ensuring that the mixed solution is just added when the temperature reaches 70°C, the mixed solution addition speed is 30s / mL, and the sodium ferrocyanide solution gradually changes from light yellow to dark blue during the addition process;

[0091] (4) After the addition was completed, the mixture was kept warm for 1 h, and the suspension was centrifuged (3 times). The precipitate was retained and dried at 120° C. in vacuum (vacuum degree: 0.01 MPa) for 24 h to obtain a Prussian blue compound (denoted as HNGPB-1) with a yield of 89.10%.

[0092] The electrochemical performance of a sodium ion full battery was tested by assembling the Prussian blue compound obtained in this comparative example as the positive electrode, the polyanion compound as the negative electrode, and sodium hexafluorophosphate as the electrolyte. The test temperature was 25° C. and the test voltage range was 1.5 to 4.5 V.

[0093] It was determined that at 0.5C, the initial specific capacity was 49.5 mAh / g, and after 3 cycles the specific capacity stabilized at 29.9 mAh / g (e.g. Figure 8 The capacity retention rate is 79%.

[0094] Comparative Example 2

[0095] This comparative example provides a method for preparing a Prussian blue compound when an insufficient amount of sodium ferrocyanide is added, and the specific steps are as follows:

[0096] (1) Weigh 0.8 mmol of ferrous chloride (FeCl2) and 0.2 mmol of nickel chloride (NiCl2) and dissolve them in 100 mL of anhydrous ethanol to form a mixed solution with a total concentration of 10 mM;

[0097] (2) Weigh 1 mmol of sodium ferrocyanide (Na4[Fe(CN)6]) and dissolve it in 100 mL of anhydrous ethanol to form a light yellow sodium ferrocyanide suspension solution with a concentration of 10 mM, and add vitamin E thereto to ensure that vitamin E is the only source of reducing agent. The amount of vitamin E used is 1 times the molar equivalent of ferrous chloride;

[0098] (3) In nitrogen atmosphere (0.05m 3 / h) protection, ultrasonically treating the mixed solution of ferrous chloride and nickel chloride (ultrasonic power is 150W), and heating it to 70°C at a heating rate of 1°C / min, and at the same time, intermittently adding the mixed solution obtained in step (2) thereto, ensuring that the mixed solution is just added when the temperature reaches 70°C, and the dropping speed of the mixed solution is 30s / mL, and during the dropping process, the sodium ferrocyanide solution gradually changes from light yellow to dark blue;

[0099] (4) After the addition was completed, the mixture was kept warm for 1 h, and the suspension was centrifuged (3 times). The precipitate was retained and dried at 120° C. in vacuum (vacuum degree: 0.01 MPa) for 24 h to obtain a Prussian blue compound (denoted as HNGPB-2) with a yield of 82.70%.

[0100] The electrochemical performance of a sodium ion full battery was tested by assembling the Prussian blue compound obtained in this comparative example as the positive electrode, the polyanion compound as the negative electrode, and sodium hexafluorophosphate as the electrolyte. The test temperature was 25° C. and the test voltage range was 1.5 to 4.5 V.

[0101] It was determined that at 0.5C, the initial specific capacity was 42.4 mAh / g, and after 3 cycles the specific capacity stabilized at 34.7 mAh / g (e.g. Fig. 9 The capacity retention rate is 77%.

[0102] Comparative Example 3

[0103] This comparative example provides a method for preparing a Prussian blue compound using deionized water as a solvent, and the specific steps are as follows:

[0104] (1) Weigh 0.8 mmol of ferrous chloride (FeCl2) and 0.2 mmol of nickel chloride (NiCl2) and dissolve them in 100 mL of deionized water to form a mixed solution with a total concentration of 10 mM;

[0105] (2) Weigh 1 mmol of sodium ferrocyanide (Na4[Fe(CN)6]) and dissolve it in 100 mL of deionized water to form a 10 mM sodium ferrocyanide solution, to which vitamin E is added to ensure that vitamin E is the only source of reducing agent, and the amount of vitamin E used is 1 times the molar equivalent of ferrous chloride;

[0106] (3) In nitrogen atmosphere (0.05m 3 / h) protection, ultrasonically treating the mixed solution of ferrous chloride and nickel chloride (ultrasonic power is 150W), and heating it to 70°C at a heating rate of 1°C / min, and at the same time, intermittently adding the mixed solution obtained in step (2) thereto, ensuring that the mixed solution is just added when the temperature reaches 70°C, and the dropping speed of the mixed solution is 30s / mL, and during the dropping process, the sodium ferrocyanide solution gradually changes from light yellow to light blue;

[0107] (4) After the addition was completed, the mixture was kept warm for 1 h, and the suspension was centrifuged (3 times). The precipitate was retained and dried at 120° C. in vacuum (vacuum degree: 0.01 MPa) for 24 h to obtain a Prussian blue compound (denoted as HNGPB-3) with a yield of 79.20%.

[0108] The electrochemical performance of a sodium ion full battery was tested by assembling the Prussian blue compound obtained in this comparative example as the positive electrode, the polyanion compound as the negative electrode, and sodium hexafluorophosphate as the electrolyte. The test temperature was 25° C. and the test voltage range was 1.5 to 4.5 V.

[0109] It was determined that at 0.5C, the initial specific capacity was 26.2 mAh / g, and after 3 cycles the specific capacity stabilized at 22.3 mAh / g (e.g. Fig.10 The capacity retention rate is 83%.

[0110] The various embodiments in this specification are described in a progressive manner, and each embodiment focuses on the differences from other embodiments. The same or similar parts between the various embodiments can be referenced to each other.

[0111] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A Prussian blue compound, characterized in that The chemical formula of the Prussian blue compound is FeR[Fe(CN)6], and the Prussian blue compound includes two weakly coordinated octahedrons FeN6 and RN6, and one strongly coordinated octahedron FeC6, wherein R represents a transition metal, and the transition metal includes nickel, manganese or cobalt; In the weakly coordinated octahedron, Fe and R are in a high spin state; The Fe in the strongly coordinated octahedron is in a low spin state; The Prussian blue compound also includes alkali metal ions, and the alkali metal ions are located in the interstitial positions of the octahedron.

2. The method for preparing the Prussian blue compound according to claim 1, characterized in that: The steps include: Mixing a transition metal salt, ferrous chloride and an anhydrous organic solvent to obtain a first mixed solution; mixing sodium ferrocyanide, a reducing agent and an anhydrous organic solvent to obtain a second mixed solution; Under an inert atmosphere, dropwise adding the first mixed solution into the second mixed solution and heating for reaction to obtain the Prussian blue compound; The transition metal salt includes nickel chloride, manganese chloride or cobalt chloride.

3. The preparation method according to claim 2, characterized in that: The total concentration of the transition metal salt and ferrous chloride in the first mixed solution is 10mM, wherein the concentration of ferrous chloride is 8-10mM, the concentration of the transition metal salt is 0-2mM, and the concentration of the transition metal salt is not 0; and / or the concentration of sodium ferrocyanate in the second mixed solution is 10mM.

4. The preparation method according to claim 2, characterized in that: The anhydrous organic solvent is anhydrous ethanol; the reducing agent includes one or more of vitamin A, vitamin C, vitamin E and beta-carotene.

5. The preparation method according to claim 2, characterized in that: The amount of the reducing agent used is 0.1 to 1 times the molar equivalent of ferrous chloride.

6. The preparation method according to claim 2, characterized in that: The step of dripping the first mixed liquid into the second mixed liquid and heating the mixture comprises: under an inert atmosphere, gradually dripping the first mixed liquid into the second mixed liquid subjected to ultrasonic treatment, heating the mixture while dripping, ensuring that the temperature is raised to the heating reaction temperature while the dripping is completed, and then keeping the temperature.

7. The preparation method according to claim 6, characterized in that: The inert gas in the inert atmosphere includes nitrogen or argon, and the flow rate of the inert gas is 0.05-0.1 m 3 / h; and / or, the ultrasonic power of the ultrasonic treatment is 100-200W; the drop acceleration of the first mixed solution is 24-36s / mL; the heating rate is 1-2°C / min; and / or, the temperature of the heating reaction is 60-80°C, and the insulation time of the heating reaction is 0.5-1.5h.

8. The preparation method according to claim 2, characterized in that: After the reaction is completed, the steps of sedimentation and drying are also included.

9. Use of the Prussian blue compound according to claim 1 in the preparation of sodium ion batteries.

10. A sodium ion battery, characterized in that: The positive electrode material of the sodium ion battery is the Prussian blue compound according to claim 1.

Citation Information

Cited By

  • Fe-free Prussian blue analogue, preparation method thereof and solid energy storage material

    CN121591229A